Digital Tax Transformation: The Impact of Online Tax Systems on Local Taxpayer Compliance in Pringsewu Regency - Tri Sari Werdoningsih; Saring Suhendro; Ninuk Dewi K (Journal of Social Research, 2026)
Low taxpayer compliance is still the main challenge in optimizing regional tax revenues, so it is necessary to innovate tax services that are easier, more efficient, and more transparent. The implementation of the online tax system is expected to encourage increased compliance of regional taxpayers through easy access and acceleration of the administrative process. This research aims to analyze the impact of the implementation of an online tax system on local taxpayer compliance in Pringsewu Regency. The method used is qualitative research with a descriptive approach through literature review and secondary data analysis supported by questionnaire results in the thesis as the primary source. Data collection techniques were conducted through literature review and document analysis, while data analysis was performed descriptively by interpreting empirical findings and relating them to relevant theories. The research results indicate that the implementation of the online tax system received a very good rating with an average of 4.30, reflecting the system’s ease of use, security, and efficiency, while the level of taxpayer compliance fell into the fairly good category with an average of 3.52 or 70.41%, with strengths in payment compliance and weaknesses in voluntary reporting. These findings indicate that the online tax system contributes positively to increased compliance but has not yet fully encouraged voluntary compliance. This study concludes that the optimization of the online tax system must be accompanied by improved education and service quality to enhance taxpayer compliance sustainably.